Vaccimel immunization is associated with enhanced response to treatment with anti-PD-1 monoclonal antibodies in cutaneous melanoma patients - a case reports study - Mordoh, José; Schwab, Erika; Bravo, Alicia Inés; Aris, Mariana; Barrio, María Marcela (Frontiers in Immunology, 2024)
Cancer vaccines are gaining ground as immunotherapy options. We have previously demonstrated in cutaneous melanoma (CM) patients that adjuvant treatment with VACCIMEL, a mixture of four irradiated CM cell lines co-adjuvanted with BCG and GM-CSF, increases the cellular immune response to melanocyte differentiation antigens, cancer-testis antigens, and neoantigens, with respect to basal levels. On the other hand, it is also known that treatment with anti-PD-1 monoclonal antibodies (MAbs), acting on pre-existing tumor-reactive lymphocytes, induces clinical responses in CM patients, albeit in a fraction of treated patients. A combination of both treatments would appear therefore desirable. In this paper, we describe CM patients who, having progressed even years after vaccination, were treated with anti-PD-1 MAbs. In 5/5 of such progressor patients, complete responses were obtained which lasted between 3 and 65+ months. Three of the patients remain disease-free and two recurred. One of the patients passed away after a recurrence of brain metastases. We suggest that clonally expanded reactive lymphocytes induced by VACCIMEL partially remain as memory cells, which may be recalled after tumor recurrence and may foster ulterior activity of anti-PD-1 MAbs.